Determination, Evaluation and Comparison of the Antioxidant Activities and Nutritional Composition of Cucurbita maxima and Vigna unguiculata Leaf Extracts - Sha’a , K. K. (Emerging Challenges in Agriculture and Food Science Vol. 4, 2022)
Antioxidant activities and nutritional composition are essential ingredients normally considered in the choice of vegetables for human consumption. Leafy vegetables in particular, are regarded as protective foods in human diet due to their many health benefits. The aim and objectives of this research was to determine, evaluate and compare the antioxidant activities and nutritional composition of leaf extracts of Cucurbita maxima and Vigna unguiculata. It was also the objective of this work, to determine the quantitative phytochemical content of experimental plants’ extracts. Quantitative analysis revealed the phytochemicals in C. maxima and V. unguiculata as; saponins (1.03%, and 1.34%), tannins (3.49% and 2.60%), terpenoids (0.0% and 0.47%), flavonoids (2.81% and 4.11%), alkaloids (5.72% and 3.5%), phenols (4.02% and 3.83%) respectively. There was a significant (p=0.05) difference in radical scavenging activity of ethanol leaf extract of V. unguiculata comprared to C. maxima. In FRAP both plants’ extract revealed a good antioxidant reducing power at 100mg/ml (range 0.40 to 0.5 absorbance) at 700nM. Antioxidant activities of extracts is attributed to their flavonoid and phenolic contents. Proximate analysis revealed the nutrients for C. maxima and V. unguiculata as; crude protein (11.58% and 14.83%), crude fat (0.47% and 0.61%), ash (4.11% and 3.72%), crude fiber (6.95 and 4.68%), moisture (1.03% and 1.38%), carbohydrate (75.86% and 74.78%) respectively. This shows that the leaves are a good source of energy to both humans and animals. Also, both vegetables revealed good percentages of proteins which can be used to compliment other sources of protein.